PERAN DINAS PERHUBUNGAN DALAM PENGELOLAAN LPJU DI KOTA PEKANBARU TAHUN 2021-2022 - Ichsan, Ali Muhamad; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Public Street Lighting Lamps (LPJU) are road equipment which is useful for supporting security, safety and order as well as adding to the beauty of the environment. The Pekanbaru City Government has issued regulations regarding instructions for installing Public Street Lighting Lamps (LPJU) in Pekanbaru City with Mayor Regulation Number 19 of 2010. The aim of this research is to determine the role of the Transportation Service in Managing LPJU in Pekanbaru City in 2021-2022. This research method uses qualitative methods with descriptive research type. The type of research data used in this research is descriptive research, namely presenting the results of research on the Role of the Transportation Service in Management of LPJU in Pekanbaru City in 2021-2022. Then the research location is the Pekanbaru City Transportation Department. Data collection techniques in this research are interview, documentation and observation techniques. The findings in this research are that the role of the Transportation Service in the Management of LPJU in Pekanbaru City in 2021-2022 in its implementation has not been maximized. It is known that in terms of organizational readiness to implement the care and maintenance program for public street lighting in terms of human resources, supporting facilities and infrastructure and the budget is still is not sufficient so that many activities cannot be carried out, such as changing lights with a limited number of lamps available, therefore it is not in accordance with the established plan. Keywords: Role, Management, Public Street Lighting